Ecology and restoration potential of Ruppia maritima in a managed mosquito impoundment of the Indian River Lagoon, Florida, USA - Deanna F. Webber; Richard E. Mulroy; Patrick H. Monaghan; David C. Heuberger; M. Dennis Hanisak; Rachel A. Brewton (Regional Studies in Marine Science, 2026)

Long‐term changes to plankton communities in artificially heated lakes - Kingsly C. Beng; Slawek Cerbin; Michael T. Monaghan; Justyna Wolinska (Limnology and Oceanography, 2025)
Increased surface‐water temperatures and nutrient enrichment are predicted to alter planktonic communities, impacting biodiversity and ecosystem functioning. While short‐term mesocosm studies have reported temperature‐ and nutrient‐driven effects, long‐term observations from natural systems remain limited. We studied seasonal plankton communities in 10 lakes in central Poland, five warmed by power plant discharge for six decades and ~ 2°C warmer (annual mean) than control lakes. Based on environmental DNA (eDNA) relative read abundance, green algae (Chlorophyta) were up to 15% more abundant in heated lakes, while golden algae (Chrysophyceae) were up to 7% more abundant in control lakes. Heated lakes exhibited higher diversity of diatoms, green algae, golden algae, cercozoans, basidiomycetes, and chytrids, especially in summer. Their plankton assemblages were compositionally distinct and showed reduced seasonal variability. Multiple regression revealed that rising temperature, interacting with elevated nutrients, reduced diversity in many plankton groups. Warming favored heat‐adapted taxa, driving compositional shifts. By providing insights into the long‐term impacts of anthropogenic warming, this study underscores the importance of integrating temperature‐nutrient interactions in predicting ecosystem responses to climate change.

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Exploring age-related differences in the relationship between spatial and temporal contributions to step length asymmetry during split-belt adaptation - Patrick G. Monaghan; William M. Murrah; Kristina A. Neely; Harrison C. Walker; Jaimie A. Roper (Experimental Brain Research, 2024)
Gait adaptability is crucial for meeting environmental demands, and impaired gait adaptation increases fall risk, particularly in older adults. While prior research exists on older adults’ gait adaptation, particularly in perturbation studies, the specific contributions of temporal and spatial adaptation strategies to step length asymmetry (SLA) during split-belt treadmill walking require further examination. This study fills this gap by evaluating how distinct adaptation strategies contribute to SLA in healthy young and older adults. 19 healthy young adults (20.4 ± 1.1 years) and 19 healthy older adults (68.3 ± 8.1 years) walked on a split-belt treadmill requiring their non-dominant leg to move twice as fast as their dominant leg. Repeated measures ANOVA investigated (1) spatial and temporal contributions to SLA, (2) SLA across gait adaptation epochs, and (3) rates of adaptation and deadaptation. Older adults displayed reduced temporal contributions to SLA compared to younger adults (F 1,36 = 6.42, p = .02, ŋ 2 = .15), but no group differences were observed in spatial contributions to SLA (F 1,36 = 3.23, p = .08, ŋ 2 = .082). SLA during adaptation and deadaptation did not differ by age group, nor did the rate of adaptation (F 1,34.7 = 0.594, p = .45) or deadaptation F 1,33.6 = 2.886, p = .09). These findings suggest that while older adults rely less on temporal strategies for gait adaptation, but maintain overall adaptability comparable to younger adults. Findings enhance our understanding of age-related changes in gait adaptation mechanisms and may inform targeted interventions to improve gait adaptability in older populations.

Social Vulnerabilities Among Hired Migrant and Seasonal Farmworkers During COVID-19: The Need for Employment-Based Indicators - Miranda Carver Martin; Jose Perez Orozco; J. Antonio Tovar-Aguilar; Maria C Morera; Cody Gusto; Linda S. Forst; Paul Monaghan (Journal of Agromedicine, 2024)

Phylogenomics including new sequence data of phytoplankton-infecting chytrids reveals multiple independent lifestyle transitions across the phylum - Pauline C. Thomé; Justyna Wolinska; Silke Van Den Wyngaert; Albert Reñé; Doris Ilicic; Ramsy Agha; Hans-Peter Grossart; Esther Garcés; Michael T. Monaghan; Jürgen F.H. Strassert (Molecular Phylogenetics and Evolution, 2024)

Effects of heat waves on telomere dynamics and parental brooding effort in nestlings of the zebra finch ( Taeniopygia castanotis ) transitioning from ectothermy to endothermy - Riccardo Ton; Winnie Boner; Shirley Raveh; Pat Monaghan; Simon C. Griffith (Molecular Ecology, 2023)
Heat waves are predicted to be detrimental for organismal physiology with costs for survival that could be reflected in markers of biological state such as telomeres. Changes in early life telomere dynamics driven by thermal stress are of particular interest during the early post‐natal stages of altricial birds because nestlings quickly shift from being ectothermic to endothermic after hatching. Telomeres of ectothermic and endothermic organisms respond differently to environmental temperature, but few investigations within species that transition from ectothermy to endothermy are available. Also, ambient temperature influences parental brooding behaviour, which will alter the temperature experienced by offspring and thereby, potentially, their telomeres. We exposed zebra finch nestlings to experimental heat waves and compared their telomere dynamics to that of a control group at 5, 12 and 80 days of age that encapsulate the transition from the ectothermic to the endothermic thermoregulatory stage; we also recorded parental brooding, offspring sex, mass, growth rates, brood size and hatch order. Nestling mass showed an inverse relationship with telomere length, and nestlings exposed to heat waves showed lower telomere attrition during their first 12 days of life (ectothermic stage) compared to controls. Additionally, parents of heated broods reduced the time they spent brooding offspring (at 5 days old) compared to controls. Our results indicate that the effect of heat waves on telomere dynamics likely varies depending on age and thermoregulatory stage of the offspring in combination with parental brooding behaviour during growth.

Substrate profiling of the Arabidopsis Ca2+-dependent protein kinase AtCPK4 and its Ricinus communis ortholog RcCDPK1 - Ryan Kilburn; Eric T. Fedosejevs; Devang Mehta; Faranak Soleimani; Mina Ghahremani; Jacqueline Monaghan; Jay J. Thelen; R. Glen Uhrig; Wayne A. Snedden; William C. Plaxton (Plant Science, 2023)

Associations between DNA methylation and telomere length during early life: Insight from wild zebra finches ( Taeniopygia guttata ) - Elizabeth L. Sheldon; Riccardo Ton; Winnie Boner; Pat Monaghan; Shirley Raveh; Aaron W. Schrey; Simon C. Griffith (Molecular Ecology, 2022)
Telomere length and DNA methylation (DNAm) are two promising biomarkers of biological age. Environmental factors and life history traits are known to affect variation in both these biomarkers, especially during early life, yet surprisingly little is known about their reciprocal association, especially in natural populations. Here, we explore how variation in DNAm, growth rate, and early‐life conditions are associated with telomere length changes during development. We tested these associations by collecting data from wild, nestling zebra finches in the Australian desert. We found that increases in the level of DNAm were negatively correlated with telomere length changes across early life. We also confirm previously documented effects of post hatch growth rate and clutch size on telomere length in a natural ecological context for a species that has been extensively studied in the laboratory. However, we did not detect any effect of ambient temperature during developmental on telomere length dynamics. We also found that the absolute telomere length of wild zebra finches, measured using the in‐gel TRF method, was similar to that of captive birds. Our findings highlight exciting new opportunities to link and disentangle potential relationships between DNA based biomarkers of ageing, and of physiological reactions to environmental change.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Whole‐genome analysis of multiple wood ant population pairs supports similar speciation histories, but different degrees of gene flow, across their European ranges - Beatriz Portinha; Amaury Avril; Christian Bernasconi; Heikki Helanterä; Josie Monaghan; Bernhard Seifert; Vitor C. Sousa; Jonna Kulmuni; Pierre Nouhaud (Molecular Ecology, 2022)
The application of demographic history modelling and inference to the study of divergence between species has become a cornerstone of speciation genomics. Speciation histories are usually reconstructed by analysing single populations from each species, assuming that the inferred population history represents the actual speciation history. However, this assumption may not be met when species diverge with gene flow, for example, when secondary contact may be confined to specific geographic regions. Here, we tested whether divergence histories inferred from heterospecific populations may vary depending on their geographic locations, using the two wood ant species Formica polyctena and F. aquilonia . We performed whole‐genome resequencing of 20 individuals sampled in multiple locations across the European ranges of both species. Then, we reconstructed the histories of distinct heterospecific population pairs using a coalescent‐based approach. Our analyses always supported a scenario of divergence with gene flow, suggesting that divergence started in the Pleistocene (c. 500 kya) and occurred with continuous asymmetrical gene flow from F. aquilonia to F. polyctena until a recent time, when migration became negligible (2–19 kya). However, we found support for contemporary gene flow in a sympatric pair from Finland, where the species hybridise, but no signature of recent bidirectional gene flow elsewhere. Overall, our results suggest that divergence histories reconstructed from a few individuals may be applicable at the species level. Nonetheless, the geographical context of populations chosen to represent their species should be taken into account, as it may affect estimates of migration rates between species when gene flow is spatially heterogeneous.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Role of B cells and the aging brain in stroke recovery and treatment - E. B. Engler-Chiurazzi; K. L. Monaghan; E. C. K. Wan; X. Ren (GeroScience, 2020)

JA:2021-19. Developing a Social Marketing Intervention for Heat Safety among Florida Tomato Harvesters: Preliminary Findings of Formative Research - Maria C. Morera; Paul F. Monaghan; J. Antonio Tovar-Aguilar; Fritz M. Roka (Journal of Agromedicine, 2020)

Determinants of Landscape Irrigation Water Use in Florida-Friendly Yards - Maria C. Morera; Paul F. Monaghan; Michael D. Dukes (Environmental Management, 2020)

The effects of two different doses of ultraviolet-A light exposure on nitric oxide metabolites and cardiorespiratory outcomes - Chris Monaghan; Luke C. McIlvenna; Luke Liddle; Mia Burleigh; Richard B. Weller; Bernadette O. Fernandez; Martin Feelisch; David J. Muggeridge; Chris Easton (European Journal of Applied Physiology, 2018)
Purpose The present study investigated different doses of ultraviolet-A (UV-A) light on plasma nitric oxide metabolites and cardiorespiratory variables. Methods Ten healthy male participants completed three experimental conditions, 7 days apart. Participants were exposed to no light (CON); 10 J cm 2 (15 min) of UV-A light (UVA10) and 20 J cm 2 (30 min) of UV-A light (UVA20) in a randomized order. Plasma nitrite [NO 2 − ] and nitrate [NO 3 − ] concentrations, blood pressure (BP), and heart rate (HR) were recorded before, immediately after exposure and 30 min post-exposure. Whole body oxygen utilization ( $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 ), resting metabolic rate (RMR) and skin temperature were recorded continuously. Results None of the measured parameters changed significantly during CON (all P > 0.05). $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 and RMR were significantly reduced immediately after UVA10 ( P < 0.05) despite no change in plasma [NO 2 − ] ( P > 0.05). Immediately after exposure to UVA20, plasma [NO 2 − ] was higher ( P = 0.014) and $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 and RMR tended to be lower compared to baseline ( P = 0.06). There were no differences in [NO 2 − ] or $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 at the 30 min time point in any condition. UV-A exposure did not alter systolic BP, diastolic BP or MAP (all P > 0.05). UV-A light did not alter plasma [NO 3 − ] at any time point (all P > 0.05). Conclusions This study demonstrates that a UV-A dose of 20 J cm 2 is necessary to increase plasma [NO 2 − ] although a smaller dose is capable of reducing $${{\dot{V}}}{\rm O}_{2}$$ V ˙ O 2 and RMR at rest. Exposure to UV-A did not significantly reduce BP in this cohort of healthy adults. These data suggest that exposure to sunlight has a meaningful acute impact on metabolic function.

The Benefits of Reduced Anthropogenic Climate changE (BRACE): a synthesis - Brian C. O’Neill; James M. Done; Andrew Gettelman; Peter Lawrence; Flavio Lehner; Jean-Francois Lamarque; Lei Lin; Andrew J. Monaghan; Keith Oleson; Xiaolin Ren; Benjamin M. Sanderson; Claudia Tebaldi; et al. (Climatic Change, 2018)

The potential impacts of 21st century climatic and population changes on human exposure to the virus vector mosquito Aedes aegypti - Andrew J. Monaghan; K. M. Sampson; D. F. Steinhoff; K. C. Ernst; K. L. Ebi; B. Jones; M. H. Hayden (Climatic Change, 2018)

Links between parental life histories of wild salmon and the telomere lengths of their offspring - Darryl McLennan; John D. Armstrong; David C. Stewart; Simon McKelvey; Winnie Boner; Pat Monaghan; Neil B. Metcalfe (Molecular Ecology, 2018)
The importance of parental contributions to offspring development and subsequent performance is self‐evident at a genomic level; however, parents can also affect offspring fitness by indirect genetic and environmental routes. The life history strategy that an individual adopts will be influenced by both genes and environment; and this may have important consequences for offspring. Recent research has linked telomere dynamics (i.e., telomere length and loss) in early life to future viability and longevity. Moreover, a number of studies have reported a heritable component to telomere length across a range of vertebrates, although the effects of other parental contribution pathways have been far less studied. Using wild Atlantic salmon with different parental life histories in an experimental split‐brood in vitro fertilization mating design and rearing the resulting families under standardized conditions, we show that there can be significant links between parental life history and offspring telomere length (studied at the embryo and fry stage). Maternal life history traits, in particular egg size, were most strongly related to offspring telomere length at the embryonic stage, but then became weaker through development. In contrast, paternal life history traits, such as the father's growth rate in early life, had a greater association in the later stages of offspring development. However, offspring telomere length was not significantly related to either maternal or paternal age at reproduction, nor to paternal sperm telomere length. This study demonstrates both the complexity and the importance of parental factors that can influence telomere length in early life.

Postnatal nutrition influences male attractiveness and promotes plasticity in male mating preferences - José C. Noguera; Neil B. Metcalfe; Pat Monaghan (The Science of Nature, 2017)

Interactions between parental traits, environmental harshness and growth rate in determining telomere length in wild juvenile salmon - D. McLennan; J. D. Armstrong; D. C. Stewart; S. Mckelvey; W. Boner; P. Monaghan; N. B. Metcalfe (Molecular Ecology, 2016)
A larger body size confers many benefits, such as increased reproductive success, ability to evade predators and increased competitive ability and social status. However, individuals rarely maximize their growth rates, suggesting that this carries costs. One such cost could be faster attrition of the telomeres that cap the ends of eukaryotic chromosomes and play an important role in chromosome protection. A relatively short telomere length is indicative of poor biological state, including poorer tissue and organ performance, reduced potential longevity and increased disease susceptibility. Telomere loss during growth may also be accelerated by environmental factors, but these have rarely been subjected to experimental manipulation in the natural environment. Using a wild system involving experimental manipulations of juvenile Atlantic salmon Salmo salar in Scottish streams, we found that telomere length in juvenile fish was influenced by parental traits and by direct environmental effects. We found that faster‐growing fish had shorter telomeres and there was a greater cost (in terms of reduced telomere length) if the growth occurred in a harsher environment. We also found a positive association between offspring telomere length and the growth history of their fathers (but not mothers), represented by the number of years fathers had spent at sea. This suggests that there may be long‐term consequences of growth conditions and parental life history for individual longevity.

Improving Health and Safety Conditions in Agriculture Through Professional Training of Florida Farm Labor Supervisors: Preliminary Findings of a Program Evaluation - Maria C. Morera; Paul F. Monaghan; J. Antonio Tovar-Aguilar; Sebastian Galindo-Gonzalez; Fritz M. Roka; Cesar Asuaje (Journal of Agromedicine, 2014)

Improving Health and Safety Conditions in Agriculture Through Professional Training of Florida Farm Labor Supervisors - Maria C. Morera; Paul F. Monaghan; J. Antonio Tovar-Aguilar; Sebastian Galindo-Gonzalez; Fritz M. Roka; Cesar Asuaje (Journal of Agromedicine, 2014)

Effect of 7-year application of a nitrification inhibitor, dicyandiamide (DCD), on soil microbial biomass, protease and deaminase activities, and the abundance of bacteria and archaea in pasture soils - Yan J. Guo; Hong J. Di; Keith C. Cameron; Bowen Li; Andriy Podolyan; Jim L. Moir; Ross M. Monaghan; L. Chris Smith; Maureen O’Callaghan; Saman Bowatte; Deanne Waugh; Ji-Zheng He (Journal of Soils and Sediments, 2013)

In vitro growth of microsporidia Anncaliia algerae in cell lines from warm water fish - S. Richelle Monaghan; Rebecca L. Rumney; Nguyen T. K. Vo; Niels C. Bols; Lucy E. J. Lee (In Vitro Cellular & Developmental Biology - Animal, 2011)

Ecosystem Characteristics and Summer Secondary Production in Stormwater Ponds and Reference Wetlands - Thomas S. Woodcock; Megan C. Monaghan; Karen E. Alexander (Wetlands, 2010)

Control of triceps surae stimulation based on shank orientation using a uniaxial gyroscope during gait - C. C. Monaghan; W. J. B. M. van Riel; P. H. Veltink (Medical & Biological Engineering & Computing, 2009)

Animal cell cultures in microsporidial research: their general roles and their specific use for fish microsporidia - S. Richelle Monaghan; Michael L. Kent; Virginia G. Watral; R. John Kaufman; Lucy E. J. Lee; Niels C. Bols (In Vitro Cellular & Developmental Biology - Animal, 2009)

Neurotrophic Actions of PACAP-38 and LIF on Human Neuroblastoma SH-SY5Y Cells - T. K. Monaghan; C. Pou; C. J. MacKenzie; R. Plevin; E. M. Lutz (Journal of Molecular Neuroscience, 2008)

Gross nitrogen mineralisation rates in pastural soils and their relationships with organic nitrogen fractions, microbial biomass and protease activity under glasshouse conditions - S. Mishra; H. J. Di; K. C. Cameron; R. Monaghan; A. Carran (Biology and Fertility of Soils, 2005)

Parental condition, brood sex ratio and differential young survival: an experimental study in gulls ( Larus fuscus ) - R. G. Nager; P. Monaghan; D. C. Houston; M. Genovart (Behavioral Ecology and Sociobiology, 2000)

Dissolved organic phosphorus in the coastal ocean: Reassessment of available methods and seasonal phosphorus profiles from the Eel River Shelf - E. J. Monaghan; K. C. Ruttenberg (Limnology and Oceanography, 1999)
Methods for quantifying total dissolved phosphorus (TDP) were reevaluated. High‐temperature ashing/hydrolysis (Ash/Hydrol.) and Acid Persulfate methods were examined for their ability to quantitatively convert a range of organic‐P compounds to orthophosphate. The Ash/Hydrol. method recovered on average 99% of organic‐P compounds tested, including phosphonates (compounds with C‐P bonds). Contrary to concerns voiced in prior studies, we found no P loss due to volatilization in seawater samples. Poor recovery by the Acid Persulfate method was observed for two compound classes: phosphonates and phospholipids. The Ash/Hydrol. method is recommended for routine TDP analyses. The hydrolysis of dissolved organic phosphorus (DOP) during the phosphomolybdate‐blue reaction and the subsequent overestimation of dissolved inorganic phosphorus (DIP) have long been a concern. Extent of hydrolysis of standard DOP compounds was evaluated both during this reaction and over long‐term acidified (pH 1.0)/refrigerated and unacidified/frozen storage. Eleven of 12 compounds tested hydrolyzed Seasonal DOP profiles from the Eel River Shelf quantified by the Ash/Hydrol. and Acid Persulfate methods yielded comparable results, indicating that the DOP pool at this site did not contain significant phospholipids or phosphonates, which are underrecovered by the Persulfate method. Recoveries using a third method, Nitrate Oxidation, were on average 7% lower. Surface‐water DOP exceeded DIP in summer and was apparently related to biological productivity, underscoring the need to include organic species when evaluating nutrient limitation and creating nutrient budgets.